ANALISIS KEABSAHAN PERJANJIAN JUAL BELI ONLINE SHOP SHOPEE OLEH ANAK DIBAWAH UMUR - Ilham Abdillah Farhan; Dwi Achmad Bustomi (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Shopee online shop sales and purchase agreements made by minors are still a phenomenon that is not yet understood from a legal aspect. To analyze the validity of the sale and purchase agreement, this research uses sociological juridical methods to question and collect data exploratively. This method was chosen with the aim of describing in depth various legal regulations and the factual basis of the problem being studied. This research also tests two hypotheses, namely, that the legal stipulation of every Shopee online buying and selling transaction by minors will not be recognized by law, but minors are experienced enough to have the right to carry out such transactions recognized. The results of this research found that according to the formal legal model, various applicable regulations determine that Shopee online buying and selling transactions by minors cannot be legally recognized. However, in validating the second hypothesis, through descriptive analysis of the words of the various actors who participated in this research, it shows that minors who repeatedly make Shopee online buying and selling agreements show various legal awareness and awareness of their rights which shows an effort to respect their rights. deal with adults in accordance with legal requirements. Competence is one of the conditions for the validity of an agreement. In contract law, one of the elements of competency is to look at a person's age. The age limit then becomes something that creates legal uncertainty because the limits vary in several laws and regulations. An agreement is valid according to law if the parties entering into the agreement are 21 years old and/or married.